2020
DOI: 10.1097/pai.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Foci of Programmed Cell Death-Ligand 1 (PD-L1)-positive Tumor Areas With Tumor-infiltrating Leukocytes (TILs) Evocative of a PD-1/PD-L1-related Adaptive Immune Resistance are Frequent in Merkel Cell Carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) targeting the programmed cell death 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) axis have revolutionized the treatment of patients with Merkel cell carcinoma (MCC). To date, no biomarker conditions access to these ICIs in MCC. We compared the tumor microenvironment of PD-L1+ and PD-L1− areas in a case series of MCC searching for foci evocative of PD-1/PD-L1 adaptive immune resistance. Among 58 tumors studied on digitalized serial tissue sections, 11 (19%) were concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These results confirm previously published data [10][11][12][13][14][15] and extend these observations to the identification of specific T-cell, macrophage and B-cell subsets whose presence is associated with MCPyV. Our data concerning PDL1 expression are largely consistent with those recently published by Walsh and coworkers [11], i.e., PDL1 is mainly expressed by peritumoral macrophages rather than neoplastic cells [13,23]: in our series, PDL1 expression by neoplastic cells was observed in just 22/179 (12%) cases, a slightly lower proportion than that found by Wehkamp et al and Benigni et al [24,25]. Our results are basically consistent with those of Miller et al, who showed that MCPyV-positive tumors had a strikingly more clonal intratumoral TCR repertoire than MCPyV-negative tumors [26].…”
Section: Plos Onesupporting
confidence: 93%
“…These results confirm previously published data [10][11][12][13][14][15] and extend these observations to the identification of specific T-cell, macrophage and B-cell subsets whose presence is associated with MCPyV. Our data concerning PDL1 expression are largely consistent with those recently published by Walsh and coworkers [11], i.e., PDL1 is mainly expressed by peritumoral macrophages rather than neoplastic cells [13,23]: in our series, PDL1 expression by neoplastic cells was observed in just 22/179 (12%) cases, a slightly lower proportion than that found by Wehkamp et al and Benigni et al [24,25]. Our results are basically consistent with those of Miller et al, who showed that MCPyV-positive tumors had a strikingly more clonal intratumoral TCR repertoire than MCPyV-negative tumors [26].…”
Section: Plos Onesupporting
confidence: 93%
“…In a large series of studies by Butala et al, 24 TILs status was shown to increase overall survival in patients with non-metastatic MCC. Other studies have indicated that not only the presence of TILs but also their immunologic properties are important in prognoses 25–28 . However, in our study, no research was conducted on the immunohistochemical properties of TILs.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies have indicated that not only the presence of TILs but also their immunologic properties are important in prognoses. [25][26][27][28] However, in our study, no research was conducted on the immunohistochemical properties of TILs.…”
Section: Discussionmentioning
confidence: 91%
“…This paradoxical correlation between the level of PDL-1 expression and improved outcomes has only been observed in MCC and some breast cancers [34]. Increased heterogeneity of tumor microenvironment may be another reason why some of the MCC tumors respond well to immune checkpoint inhibitors, while others may not [35]. Progress in digital pathology and multiplex immunolabeling may allow for more predictability of tissue response to immune checkpoint inhibitors prior to treatment [35].…”
Section: Diagnosismentioning
confidence: 99%